The simulation buoy shape bullet of sea wave energy absorption based on diameter variations. Issue 1 (July 2020) - Jufri,; Paroka, Daeng; Jalaluddin,; Tarakka, Rustan
Abstract: The use of fossil energy on a large scale to meet energy demand will be a threat to life in the form of air pollution, global warming and threats to the availability of fossil energy. Therefore, researchers feel it is important to conduct research with the aim of studying the potential of new and renewable energy from ocean wave energy absorption using buoys by varying the absorbent diameter of the buoyancy form. This potential is a great opportunity to meet the energy demand in coastal areas and small islands in Indonesia. This study focuses on the potential to absorb buoys carried out in transitional seas with a depth of 5.0 meters, variations in buoy diameter ranging from 1.0 meters to 10.0 meters. The wave force absorbed by the buoy is calculated using the Strip Theory Method including the kinetic force caused by the movement of the buoy. The highest efficiency of buoyancy absorption efficiency was 37.17% for floating buoys with diameter of 2.5 meters and meeting frequency of 1.379 rad/sec and the lowest 36.58% for diameter of 10.0 meters and meeting frequency of 1, 463 rad / sec.